2012
DOI: 10.1371/journal.pone.0035586
|View full text |Cite
|
Sign up to set email alerts
|

A New Cationic Porphyrin Derivative (TMPipEOPP) with Large Side Arm Substituents: A Highly Selective G-Quadruplex Optical Probe

Abstract: The discovery of uncommon DNA structures and speculation about their potential functions in genes has brought attention to specific DNA structure recognition. G-quadruplexes are four-stranded nucleic acid structures formed by G-rich DNA (or RNA) sequences. G-rich sequences with a high potential to form G-quadruplexes have been found in many important genomic regions. Porphyrin derivatives with cationic side arm substituents are important G-quadruplex-binding ligands. For example, 5,10,15,20-Tetrakis(N-methylpy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 40 publications
3
60
0
1
Order By: Relevance
“…A primary requirement for ideal ligands targeting a telomeric region is that they must have a high level of G-quadruplex-binding selectivity for other DNA structures, including duplex and single-stranded DNAs. Earlier, we showed p -TMPipEOPP could discriminate G-quadruplexes from duplex and single-stranded DNAs with a high level of specificity (47,48). To investigate the feasibility of using m -TMPipEOPP as a specific G-quadruplex ligand under molecular crowding conditions, binding interactions between m -TMPipEOPP and both monomeric and multimeric G-quadruplexes, duplex or single-stranded DNAs were investigated by following the effects of these DNAs on the UV-vis absorption spectrum of m -TMPipEOPP using polyethylene glycol 200 (PEG 200) as a molecular crowding agent, and the result was compared to p -TMPipEOPP (Figure 1 and Supplementary Figure S4).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A primary requirement for ideal ligands targeting a telomeric region is that they must have a high level of G-quadruplex-binding selectivity for other DNA structures, including duplex and single-stranded DNAs. Earlier, we showed p -TMPipEOPP could discriminate G-quadruplexes from duplex and single-stranded DNAs with a high level of specificity (47,48). To investigate the feasibility of using m -TMPipEOPP as a specific G-quadruplex ligand under molecular crowding conditions, binding interactions between m -TMPipEOPP and both monomeric and multimeric G-quadruplexes, duplex or single-stranded DNAs were investigated by following the effects of these DNAs on the UV-vis absorption spectrum of m -TMPipEOPP using polyethylene glycol 200 (PEG 200) as a molecular crowding agent, and the result was compared to p -TMPipEOPP (Figure 1 and Supplementary Figure S4).…”
Section: Resultsmentioning
confidence: 98%
“…Deionized and sterilized water (resistance > 18 MΩ/cm) was used throughout the experiments. p -TMPipEOPP was synthesized according to the method reported by us (48). The details of synthesis and characterization of m -TMPipEOPP are available in Supporting Information (Supplementary Figures S1–S3).…”
Section: Methodsmentioning
confidence: 99%
“…Although the widely studied G-quadruplex ligand 5,10,15,20-tetrakis(N-methylpyridinium-4-yl)-21H,23H-porphyrin (TMPyP4, Scheme 1) shows attractive G-quadruplex-stabilizing ability, it lacks selectivity against duplex DNA (24). Recently, by changing the small side arm methylpyridine substituents of TMPyP4 to larger [2-(1-methyl-1-piperidinyl) ethoxy] phenyl substituents, our group synthesized a new cationic porphyrin derivative 5,10,15,20-tetra-{4-[2-(1-methyl-1-piperidinyl)ethoxy] phenyl} porphyrin (TMPipEOPP, Scheme 1) and found that it could be used as a highly specific optical probe for discriminating monomeric G-quadruplexes from duplex and single-stranded DNAs under dilute conditions (25). We also demonstrated that the binding stoichiometry of TMPipEOPP to monomeric G-quadruplexes changed with the G-quadruplex/TMPipEOPP concentration ratio (25).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, by changing the small side arm methylpyridine substituents of TMPyP4 to larger [2-(1-methyl-1-piperidinyl) ethoxy] phenyl substituents, our group synthesized a new cationic porphyrin derivative 5,10,15,20-tetra-{4-[2-(1-methyl-1-piperidinyl)ethoxy] phenyl} porphyrin (TMPipEOPP, Scheme 1) and found that it could be used as a highly specific optical probe for discriminating monomeric G-quadruplexes from duplex and single-stranded DNAs under dilute conditions (25). We also demonstrated that the binding stoichiometry of TMPipEOPP to monomeric G-quadruplexes changed with the G-quadruplex/TMPipEOPP concentration ratio (25). At high ratios, a single TMPipEOPP molecule stacked between the ends of two monomeric G-quadruplexes like a sandwich, implying that TMPipEOPP might be developed into a ligand targeting the multimeric G-quadruplex structure (25).…”
Section: Introductionmentioning
confidence: 99%
“…Bulky porphyrin derivatives H 2 -TMPipEOPP, H 2 -TMPy2PP, H 2 -GP, H 2 -DIGPor and H 2 -TPyEtCAP can perfectly discriminate between quadruplex and double-stranded DNA [63,69,71,[116][117][118][119][120]. Their binding constants for quadruplex DNA is comparable to that of best G4 ligands [120].…”
Section: Interaction Of Porphyrins With G-quadruplex Dnamentioning
confidence: 96%